Comprehensive multi-scale cylinder lubrication model for reciprocating piston compressors: From rigid-body dynamics to lubricant-flow simulation. (February 2023) - Fritz, Bernhard; Scheichl, Bernhard
Abstract: A new comprehensive cylinder lubrication model for reciprocating piston compressors is presented. The focus lies on deriving the oil transport along the piston assembly to obtain compressor specific, optimal lube strategies without neglecting any main driver for oil consumption. The model accounts for the mutual interactions between the oil film, the compressed gas, the piston- and rider rings, the piston motion, the bending of the piston rod, and the crosshead motion. The presented model deals with the dynamical behavior of the entire drive including the secondary piston movements. A starving number St is introduced to study the tribological conditions between rings and cylinder wall and to assess the impact of starved lubrication. Graphical abstract: